2017
DOI: 10.1111/arcm.12330
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Variability in the Paredón Obsidian Source, Puebla and Hidalgo, Mexico: A Preliminary Assessment and Inter‐Laboratory Comparison

Abstract: Chemical characterization reveals intra-source variation in obsidian from the Paredón source area in Puebla and Hidalgo, Mexico. Two chemical sub-sources of obsidian from Paredón are spatially discrete and cannot be distinguished by visual characteristics. To facilitate future investigations of the prehistoric exploitation of these sub-sources, an inter-laboratory comparison of elemental concentrations is presented based on neutron activation analysis and several XRF instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Our main objective is to identify if changes in the exchange networks came from the political control of the El Pared on source or through independent procurement strategies. But in order to pursue this objective it is essential to detect if most of the obsidian present at the Formative period sites arrived from the El Pared on source, as part of a larger volcanic center related to the Tulancingo-Acoculco Caldera Complex, or perhaps from a specific subsource within the same caldera (L opez-Hern andez et al, 2009;Millhauser et al, 2017). Previous research related to volcanic deposits and different volcanic caldera formations at El Pared on has shown variation in the formation of this region that can provide important information allowing for a more specific characterisation of the source.…”
Section: A New Program Of Subsource Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Our main objective is to identify if changes in the exchange networks came from the political control of the El Pared on source or through independent procurement strategies. But in order to pursue this objective it is essential to detect if most of the obsidian present at the Formative period sites arrived from the El Pared on source, as part of a larger volcanic center related to the Tulancingo-Acoculco Caldera Complex, or perhaps from a specific subsource within the same caldera (L opez-Hern andez et al, 2009;Millhauser et al, 2017). Previous research related to volcanic deposits and different volcanic caldera formations at El Pared on has shown variation in the formation of this region that can provide important information allowing for a more specific characterisation of the source.…”
Section: A New Program Of Subsource Samplingmentioning
confidence: 99%
“…Despite the difficulty, the authors established the importance of the El Pared on source for the development of Mesoamerican societies, particularly during the Formative period. Millhauser et al (2017) more recently performed a geochemical analysis with INAA and XRF on 16 geological artifacts obtained from El Pared on. Through their study, they identified two spatial and statistical conglomerates that were named Pared on-A and Pared on-B.…”
Section: The El Pared On Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…To determine the source of the obsidian exploited for the artefacts in the British Museum, we used a portable XRF (pXRF) instrument (Niton XL3T 980 GOLDD+). The use of pXRF analysis has been successful in determining the geological sources of artefacts in many parts of the world (Craig et al 2007;Millhauser et al 2011Millhauser et al , 2018Frahm et al 2014). Our analytical procedure followed a well-established methodology (Campbell & Healey 2016).…”
Section: Geological Provenance Of the British Museum Mirrorsmentioning
confidence: 99%
“…To date, the study of obsidians has for the most part been conducted using macroscopic observation and bulk analytical measurement tools, typically using a combination of large area x-ray fluorescence (XRF) for major elements, while trace elements are measured using alternate techniques such as neutron activation analysis (NAA), and are always combined with visual inspection/classification for color. Generally, Obsidian consists of oxides of Si, Al, Fe, Ca, Na, K, Ti, Mn and Mg, with a range of trace elements that can include a large fraction of the periodic table: Ba, Ce, Cl, Cr, Co, Cs, Cu, La, Nb, Nd, Ni, Pb, Rb, Sc, Sr, Ta, Th, Y, U, Zn, and Zr depending upon the source [1][2][3]. Overall, SiO2 generally makes up > 70% of the content of the glass.…”
mentioning
confidence: 99%